Electrical Transport Analysis using Two Different Hopping Models on Pr0.75Na0.25Mn1-xCrxO3 Manganite: Electrical Transport Analysis using Two Different Hopping Models on Pr0.75Na0.25Mn1-xCrxO3 Manganite - Farizah, Nur Hazzanita; Suhadir Shamsuddin (Enhanced Knowledge in Sciences and Technology, 2022)
By fitting the theoretical equation with experimental data of susceptibilityand resistivity values, the half-doped for Pr0.75Na0.25Mn1-xCrxO3 (x = 0, 0.02 and 0.04) manganite has been analyzed. Small polaron hopping (SPH) and variable rangehopping (VRH) models were used to fit the electrical resistivity data at the insulating region, which ranged from 300 K to 75 K. The value of hopping and activation energywas discovered to change as a result of the influence of Cr content in the sample manganite. Thus, this behavior was proposed as a result of the weakening of the Jahn-Teller (JT) distortion caused by a decrease in the Mn3+/Mn4+ ratio, which would influence the CO state. The values of the square linear coefficient (R2 ) were examined in order to select the best model for describing electrical resistivity behavior. As a result of the greater value of R2 , it can be shown that Variable Range Hopping (VRH) was chosen as the best model for explaining an electrical resistivity behavior.